A STUDY ON SOCIAL SUPPORT FROM FAMILY AND WORK-RELATED STRESS AMONG RAILROAD WORKERS - Rizki Amalia; Nayla Kamilia Fithri; Farahdina Bachtiar (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2020)
Background: Stress is unavoidable nowadays, especially work-related stress. Everyone can experience it, including railroad workers, because of their nature of the job is related to the safety of other people. Occupational stress can be minimized by social support from the family. The objective of this study was to analyze the association between support given from family with work-related stress among railroad workers. Method: A cross-sectional study with 202 respondents as the research’s sample using purposive sampling method, consist of Train Drivers, Train Driver Assistants, Train Conductors, Railway Traffic Controller, and Railway Crossing Attendants. The instrument used by this research was NIOSH Generic Job Stress Questionnaire. Result: The majority of respondents had tremendous support from their families. Respondents experienced work-related stress caused by the lack of physical environment, high quantitative workload, high variance in workload, high responsibility for other people’s safety, and high mental demands. There was a significant association between social support from family and work-related stress among railroad workers (p-value <0,001). Discussion: Workers with low social support from family were 5-14 times more likely to experience work-related stress compared to the worker with high social support from family.